AS FORMAS DE VIOLÊNCIA CONTRA A MULHER NO MUNICÍPIO DE TIMON- (MA) - Silva, Maria de Fátima Parentes da (2008)
Introduction: Violence against women is a global problem of public health and violate principles of equality. Spite of all earned rights, existent laws, and public policies that have been introduced, women keep on suffering from violence. Objectives: We studied the various forms of violence, the characteristics of the victim and the relationship with the abuser. Methods: We conducted a retrospective and descriptive study, July to December 2005, the Medical Legal Institute (IML) of the city of Timon-MA with women who have suffered some type of violence and tried to go to the Special Care Women ( DEAM) for record of the police reports (BO), being sent to the IML to the implementation of peer review. Results: Of the 106 cases studied, 78% were of physical violence inflicted by white gun, sticks, stones, feet, hands and teeth. In 52% of cases the hand was used to strike and strangle. In 61% the lesions were multiple women presenting with 2 or up to 5 types of injuries such as bruises (34%) and excoriation (27%). As the location of the lesions, 30% were in the head and upper limbs 34%, which demonstrates the intention of the brutal aggressor in hurt and leave visible marks, since 79% was observed in the presence of harm to physical integrity of women. Sexual violence was reported in 13 cases, in which 54% of women were raped. Conclusions: The information collected from the IML showed that violence against women does not restrict itself to a certain age, race, profession or marital status and in 54% of assaults, the perpetrator was known by the woman, of which 44% were husband / boyfriend.